Cost-effectiveness of Prosorba column therapy for rheumatoid arthritis: a framework for analysis. - Griffiths, R; Slurzberg, J (2001)
Apheresis with the Prosorba column is safe and effective for treating refractory rheumatoid arthritis. It also is resource intensive. Economic evaluation of Prosorba column therapy could help promote efficient use of this technology. This article describes a framework and the data requirements for analyzing the cost-effectiveness of Prosorba column therapy. Several factors are considered in developing the framework including the target patient population, treatment alternatives, and clinical, economic, and quality of life outcomes of alternative treatments. We propose decision modeling as the appropriate study design because it provides a flexible framework for combining and analyzing data from different sources including experimental and nonexperimental studies. The cost-effectiveness of Prosorba column therapy will depend on the patient population in which it is used and the other treatment options still available to these patients. Offsets to the costs of providing Prosorba column therapy are likely to be largest in treatment-refractory patients and when this therapy is compared to other expensive new agents such as etanercept.